Advances in immune microenvironment and immunotherapy strategy for colorectal cancer - Yang Changjiang; Zhao Long; Lin Yilin; Ye Yingjiang; Wang Shan; Shen Zhanlong (结直肠肛门外科)
Immunotherapy, represented by immune checkpoint inhibitors, has opened a new era of tumor treatment. Increasing evidence have shown that the immune microenvironment plays an important role in the occurrence and development of colorectal cancer. T cells, B cells, macrophages, and other immune cells together constitute a complex immune microenvironment and participate in the development and progression of colorectal cancer. Understanding the degree of infiltration and function of different types of immune cells in the immune microenvironment of colorectal cancer is of great significance for evaluating the prognosis and mining potential therapeutic targets. This article reviewed the role of different types of immune cells in colorectal cancer and summarized the current progress of colorectal cancer immunotherapy to provide a scientific basis for optimizing immunotherapy for colorectal cancer.